Synthesis of Optically Pure (S,E)-2-Amino-5-arylpent-4-enoic Acids by Heck Reactions of Nickel Complexes - Parpart, Silvio; Mardiyan, Zorayr Z.; Ehlers, Peter; Petrosyan, Andranik; Mkrtchyan, Anna F.; Saghyan, Ashot S.; Langer, Peter (Synlett, 2018)
Starting from commercially available building blocks a variety of enantiomerically pure (S)-2-amino-4-enoic acids has been synthesized by the Heck reaction using Ni-(S)-BPB {Nickel-N-[(S)-benzylprolyl]aminobenzophenone} as a chiral auxiliary. The reactions proceeded in very good yields and with high E-selectivity.
Keywords: amino acids; Heck reaction; catalysis; chiral auxiliary; enantioselectivity